Getting to know Xindice an open source native XML database. - Mimaroglu, Selim
Apache Software Foundation's XIndice is an open source native XML database. Apache provides great software to developers such as the Apache Web Server, Tomcat Application Server, Cocoon Web Development Framework, Struts Framework, Ant and many more uder an open source license. Apache Web Server is an industrial strength product that is used by many high-traffic Web sites. Apache Tomcat is a servlet container that implements both Java Servlets and Java Server Pages. The fact that Xindice is a member of the Apache Software Foundation gives it substantial credibility, because Apache produces well-known, well-respected software. We will explore the XIndice native XML database beginning with its installation and advancing step by step. As the Xindice home page suggests, you are encouraged to pronounce it as "zeen-dee-chay" with your best faux Italian accent. Xindice supports XPath query language, XML : DB and XUpdate standards in Java, in addition to XML-RPC API for non-Java programmers.